2017
DOI: 10.3390/coatings7020023
|View full text |Cite
|
Sign up to set email alerts
|

Silicides and Nitrides Formation in Ti Films Coated on Si and Exposed to (Ar-N2-H2) Expanding Plasma

Abstract: Abstract:The physical properties including the mechanical, optical and electrical properties of Ti nitrides and silicides are very attractive for many applications such as protective coatings, barriers of diffusion, interconnects and so on. The simultaneous formation of nitrides and silicides in Ti films improves their electrical properties. Ti films coated on Si wafers are heated at various temperatures and processed in expanding microwave (Ar-N 2 -H 2 ) plasma for various treatment durations. The Ti-Si inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
3
16
1
Order By: Relevance
“…A longer exposure time up to 3 h results in a decrease of both TiN and TiO 2 reflection line intensities ( Figure 4b). Hydrogen species as NH x radicals and/or H atoms produced in (Ar-N 2 -H 2 ) plasma have a reducing effect on oxide species, which form in the surface layers of metal films such as Ti [15]. However, as far as TiN is concerned, hydrogen species could also have an etching effect on TiN during the first stages of crystallization.…”
Section: Xrd Investigationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A longer exposure time up to 3 h results in a decrease of both TiN and TiO 2 reflection line intensities ( Figure 4b). Hydrogen species as NH x radicals and/or H atoms produced in (Ar-N 2 -H 2 ) plasma have a reducing effect on oxide species, which form in the surface layers of metal films such as Ti [15]. However, as far as TiN is concerned, hydrogen species could also have an etching effect on TiN during the first stages of crystallization.…”
Section: Xrd Investigationsmentioning
confidence: 99%
“…Raman spectroscopy measurements carried out on Mo-Ti bilayer films processed at 600 and 800 • C confirm the XRD results ( Figure 5). as low as 400 °C , before various titanium silicides are formed at higher temperatures [15], interdiffusions of Si and Mo occurred at the Mo-Si interface and MoSi2 crystallizes at substrate temperatures of 800 °C . TiO2 in rutile phase is detected in the film instead of anatase phase (Figure 4c).…”
Section: Raman Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The good affinity between the O atoms and the active Fe atoms prompts the formation of Fe 3 O 4 (FeO·Fe 2 O 3 ), as illustrated by the XPS result in Figure 15. It was reported that the formation of iron oxide contributes to the improvement of the friction coefficient [25,26]. Nitrogen elements were not detected in the E and F regions for the modified F3 film, and the higher Cu content in the film layer indicates the existence of Cu-Ti intermetallics of higher Cu/Ti atomic ratios and the Cu grains, which are of lower hardness, so the WC ball penetrates into the substrate during the sliding test.…”
Section: Resultsmentioning
confidence: 93%
“…The good affinity between the O atoms and the active Fe atoms prompts the formation of Fe3O4 (FeO·Fe2O3), as illustrated by the XPS result in Figure 15. It was reported that the formation of iron oxide contributes to the improvement of the friction coefficient [25,26]. In addition, the high O content might result from the oxidation of Ti-N compounds, which also led to the decreasing amounts of Ti-N compounds [5], as well as the formation of the iron oxide (Fe 3 O 4 ) during the plasma nitrating process and the wear-test process.…”
Section: Resultsmentioning
confidence: 99%